Strategi Pengelolaan Modal Kerja untuk Meningkatkan Efisiensi Usaha pada UMKM - Widiastuti, Maria; Widowati, Dorina; Kusumasari, R.A. Hera Purnami; Kartika, Nurmaya; Karlina, Yuniasari (PT. Cendekia Sapta Indonesia, 2025)
Micro, small, and medium enterprises (MSMEs) play a crucial role in Indonesia’s economy as they absorb a large workforce and contribute significantly to national GDP. However, one of the main challenges faced by MSMEs, including Rufata MSME in Pancoran, South Jakarta, is ineffective working capital management. Poor management often results in excessive inventory, uncollectible receivables, or the use of funds for non-productive purposes, which in turn reduces business efficiency. To address this issue, the Faculty of Economics and Business, Trisakti University, conducted a Community Service program in the form of a working capital management training for Rufata MSME entrepreneurs. The program consisted of need assessment, preparation of training modules, face-to-face workshops, simulation of working capital calculation, and mentoring on effective working capital management strategies. A total of 20 participants actively involved in Rufata MSME joined the program. Evaluation was carried out using pre-test and post-test questionnaires to assess participants’ understanding of working capital concepts, calculation methods, benefits of efficiency, and alternative sources of financing. The results indicated a significant improvement in participants’ knowledge, as reflected in higher post-test scores and positive feedback on training relevance. This program demonstrates that practice-based training helps MSME entrepreneurs better understand and implement effective working capital management. Future initiatives should expand to other MSME groups to strengthen overall microenterprise performance in Indonesia.